Observations on little-known Phaseolus germplasm of Ecuador - Debouck, Daniel G.; Castillo T., R.; Tohme, Joseph M. (1989)
No wild Phaseolus bean germplasm is currently available from seed banks for Ecuador. Because of the decisive importance of the wild forms in evolutionary studies of the bean crops, and given the key geographical situation of that country in the northern Andes, a joint exploration was recently carried out in six provinces of northern and central Ecuador by Centro Internacional de Agricultura Tropical (CIAT), the International Board for Plant Genetic Resources (IBPGR) and Instituto Nacional de Investigaciones Agropecuarias (INIAP). The discovery of wild P. vulgaris and P. lunatus is discussed in relation to the problem of domestication of these two cultigens in the Andean context. (AS)